Usefulness of a selective neutrophil elastase inhibitor, sivelestat, in acute lung injury patients with sepsis - Miyoshi S; Hamada H; Ito R; Katayama H; Irifune K; Suwaki T; Nakanishi N; Kanematsu T; Dote K; Aibiki M; Okura T; Higaki J (Dove Medical Press, 2013)
Seigo Miyoshi,1 Hironobu Hamada,1,2 Ryoji Ito,1 Hitoshi Katayama,1 Kazunori Irifune,1 Toshimitsu Suwaki,3 Norihiko Nakanishi,4 Takanori Kanematsu,5 Kentaro Dote,6 Mayuki Aibiki,7 Takafumi Okura,1 Jitsuo Higaki1 1Department of Integrated Medicine and Informatics, Ehime University, Graduate School of Medicine, Toon, 2Graduate School of Biomedical and Health Sciences, Hiroshima University, Hiroshima, 3Department of Respiratory Medicine, Sumitomo Besshi Hospital, Niihama, 4Department of Respiratory Medicine, Ehime Prefectural Central Hospital, Matsuyama, 5Department of Respiratory Medicine, Matsuyama Red Cross Hospital, Matsuyama, 6Intensive Care Division, Ehime University Hospital, Toon, 7Department of Emergency Medicine, School of Medicine, Ehime University, Toon, Japan Background: Neutrophil elastase plays a crucial role in the development of acute lung injury (ALI) in patients with systemic inflammatory response syndrome (SIRS). The clinical efficacy of the neutrophil elastase inhibitor, sivelestat, for patients with ALI associated with SIRS has not been convincingly demonstrated. The aim of this study was to determine if there are clinical features of patients with this condition that affect the efficacy of sivelestat. Methods: This was a retrospective study of 110 ALI patients with SIRS. Clinical information, including the etiology of ALI, the number of organs failing, scoring systems for assessing the severity of illness, and laboratory data, was collected at the time of diagnosis. Information on the number of ventilator-free days (VFDs) and changes in PaO2/FIO2 (ΔP/F) before and 7 days after the time of ALI diagnosis was also collected. The effect of sivelestat on ALI patients was also examined based on whether they had sepsis and whether their initial serum procalcitonin level was ≥0.5 ng/mL. Results: There were 70 patients who were treated with sivelestat and 40 control patients. VFDs and ΔP/F were significantly higher in the treated patients than in the control patients. However, there was no significant difference in the patient survival rate between the two groups. Sivelestat was more effective in ALI patients with a PaO2/FIO2 ratio ≥140 mmHg or sepsis. Sivelestat significantly prolonged survival and led to higher VFDs and increased ΔP/F in septic patients and patients with initial serum procalcitonin levels ≥0.5 ng/mL. Conclusion: The results may facilitate a future randomized controlled trial to determine whether sivelestat is beneficial for ALI patients with sepsis. Keywords: systemic inflammatory response syndrome, procalcitonin, ventilator-free days, neutrophil elastase